Genomic analysis of two drug‐resistant clinical Morganella morganii strains isolated from UTI patients in Pretoria, South Africa. (1st January 2020) - Mbelle, N.; Osei Sekyere, J.; Feldman, C.; Maningi, N.E.; Modipane, L.; Essack, S.Y.
Abstract: Morganella morganii is an opportunistic bacterial pathogen of the Enterobacteriaceae family that is occasionally isolated from clinical (animal and human) specimens with varying resistance profiles. Detailed genomic analyses of drug‐resistant M. morganii strains are relatively limited, particularly in Africa, which is also due to their relatively low isolation rates from clinical settings. Here we report on two multidrug‐resistant clinical M. morganii isolates from urine specimens of two hospitalized patients in South Africa who presented with urinary tract infections in 2013. The isolates, M006 and E042, were only susceptible to carbapenems, amikacin and tigecycline. One strain, M006, had a novel class 1 integron, ln 1484, associated with aadA7, sul1 and gcuD gene cassettes and a Col3M plasmid replicase gene. The ln 1484 intI1 : aadA7:sul1 genes were bracketed by a Tn As3 composite transposon while a tet (B) gene was found on an IS 4 family transposon. The rare bla DHA‐4 and bla DHA‐1 AmpC β‐lactamase genes were identified on the isolates' chromosome. The isolates were phylogenetically distant and closely related to other international strains, suggesting that they were not obtained from a single epidemiological source. Further molecular surveillance is necessary to establish the prevalence of these MDR strains in the tertiary hospital. Moreover antibiotic stewardship and antibiotic sensitivity testing of all clinical isolates should be undertaken after empirical treatment to inform tailored therapy as well as reduce escalation of resistance and associated morbidities and mortalities. Significance and Impact of the Study: We report on the first clinical Morganella morganii draft genomes from Africa. The isolates were found in the urine of patients presenting with urinary tract infections (UTIs). Notably, they were resistant to important clinical antibiotics, including those used to treat UTIs. Due to the common occurrence of UTIs, particularly among pregnant women for whom drug options are limited, the presence of antibiotic‐resistant uropathogens such as M. morganii is a serious public health concern. We therefore characterized the resistance mechanisms and epidemiology of these isolates to provide further insights into their dissemination and background data for future studies.